Educational Hermeneutics of al-Hikam: A Contemplative Learning Model for Pesantren Teachers (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2025)
This article examines the Hermeneutics of Education in al-Hikam as a foundation for developing a contemplative learning model for pesantren teachers. al-Hikam, authored by Ibn ‘Atha’illah al-Sakandari, has long been understood as an ethical-spiritual Sufi text; however, its potential as a source of reflective pedagogy has not yet been systematically explored. This study employs a qualitative-hermeneutic approach by integrating philosophical hermeneutics and critical pedagogy to interpret the aphorisms of al-Hikam within the context of pesantren educational praxis. The findings indicate that the core values of al-Hikam-such as intentional awareness (niyyah), inner discipline, critique of formalism, and an orientation toward self-transformation-can be formulated into a contemplative learning model that emphasizes the integration of cognition, affection, and the teacher’s spirituality. This model positions teachers not merely as transmitters of knowledge, but as reflective subjects who continuously engage in pedagogical self-examination (muhasabah). The primary contribution of this study lies in the formulation of a conceptual framework for contemplative learning grounded in the classical Sufi tradition, which remains relevant to the contemporary challenges of pesantren teacher professionalism. These findings enrich the discourse of Islamic education by offering an alternative paradigm that balances pedagogical competence with spiritual depth as the foundation of transformative learning in pesantren.